Effect of river size on Amazonian primate community structure: A biogeographic analysis using updated taxonomic assessments. Issue 7 (23rd April 2020) - Fordham, Gail; Shanee, Sam; Peck, Mika
Abstract: The mechanisms that underlie the diversification of Neotropical primates remain contested. One mechanism that has found support is the riverine barrier hypothesis (RBH), which postulates that large rivers impede gene flow between populations on opposite riverbanks and promote allopatric speciation. Ayres and Clutton‐Brock (1992) demonstrated that larger Amazonian rivers acted as barriers, delineating the distribution limits of primate species. However, profound changes in taxonomy and species concepts have led to the proliferation of Neotropical primate taxa, which may have reduced support for their results. Using the most recent taxonomic assessments and distribution maps, we tested the effect of increasing river size on the similarity of opposite riverbank primate communities in the Amazon. First, we conducted a literature review of primate taxonomy and developed a comprehensive spatial database, then applied geographical information system to query mapped primate ranges against the riverine geography of the Amazon watershed to produce a similarity index for opposite riverbank communities. Finally, we ran models to test how measures of river size predicted levels of similarity. We found that, almost without exception, similarity scores were lower than scores from Ayres and Clutton‐Brock (1992) for the same rivers. Our model showed a significant negative relationship between streamflow and similarity in all tests, and found river width significant for the segmented Amazon, but not for multiple Amazon watershed rivers. Our results support the RBH insofar as they provide evidence for the prediction that rivers with higher streamflow act as more substantial barriers to dispersal, and accordingly exhibit greater variation in community composition between riverbanks. Abstract : Research Highlights: Species similarity on opposite banks in the Amazon was lower than expected. Streamflow and river width predicted species similarity. Results support the riverine barrier hypothesis in that river characteristics can be related to community composition.